Effects of prototype training package on attitudes and constructive participation behavior in university activities of Rajabhat University students - Panyaa, Adul; Meekhunb, Kosol; Ranongb, LaddawanNa (My University, 2018)
This research investigated using different levels of a training package on the psychological traits and constructive participation behavior of Rajabhat University students. The effect of training was studied using a combination of different levels of psychological readiness and the biosocial background of the trainees to predict the psychological traits and participating behavior after the training. The study employed experimental research. The sample consisted of Lampang Rajabhat University sophomores, who were randomly assigned into 4 groups each of which consisted of 30 students with 3 experimental groups and 1 control group. The instruments were the training package and rating scale questionnaires. The statistics used for testing the hypothesis were analysis of variance, Scheffe's method, and multiple regression analysis. The findings revealed that the effects of training using a package of different components were (1) integrated psychological training together with integrated skills tended to yield the best results when evaluated immediately and one month after the training on students' attitudes and behaviors, (2) the integrated psychological training yielded better results than the other types of training regarding the students' readiness to participate in institutional activities; and (3)integrated skill training yielded better results than any other kind of training on students' achievement motivation and intention for participating in activities when evaluated immediately. Other findings were that the level of a family's income was a combinative factor affecting the training regarding psychological traits training, attitudes, and behaviors of students when participating in the institutional activities. Finally, groups of psychological factors and situational factors together with groups of factors measured after the training predicted student's attitude and behavior when participating in the activities better than only one group of factors. Significant factors found in combination with the training factors were having a good model, achievement motivation, future orientation and self-control, constructive attitude towards participation in the activities, integrated psychological training, and integrated skill training.
full text
Keywords: attitudes behaviors prototype training package psychological traits Rajabhat University